Soft sculpture through children's artistic character / Nur Adilah Abdullah - Abdullah, Nur Adilah (2012)
Early childhood education is significant stage of life span of children's developments. This study investigates and examines children art in drawing through children's artistic character based on four items of drawing: flowers, toys, candy and cartoon. Through the four items, children can portray their environment and their knowledge, and it aims to gain insight into child behaviour and develop an appreciation of the complex and varied ways in which children grow and develop. The objective of this study is to perceive children understanding of art through artistic character, based on the 4 item: Flowers, toys, candy and cartoons and to explore a new concept can be developed by children in Malaysia at the ages 5 to 7 years old. Therefore this study reports the results of a study conducted among selected preschool in Wilayah Persekutuan and Selangor with regard to the children development in art and the perceive of children's in the 4 themes given. Children drawing at the age of five to seven were analyse, and conversation interview were also collected as data. The different approaches and perception would be discussed in the light of developmental of the stage of symbol making stages, preschamatic stage and pictorial stage. The analysis of data were presented based on cognitive development, their attitudes and children art developmental based on the evident collected. In brief, the findings are obtained based on new concepts in foundation of artanddevelopmentalof children stage. This study, concludes with the discussion of potential and relevance of children's developments through art, therefore this study can inculcates awareness amongst educators and institutions for improving children education.